Diversity and distribution of Peruvian mammals from Peru by departments and ecoregions I - Pacheco, Víctor (2020)
This work summarizes recent knowledge regarding the diversity and distribution of 11 Orders of mammals from Peru. Species information is presented for the country, ecoregions and, for the first time, by individual departments. Furthermore, we identified endemic species for the country and provided elevation ranges per species. To compile our information, we conducted an exhaustive review of the scientific literature and specimens in scientific collections, consulting with specialists when needed to verify records. We report 191 species belonging to the orders Didelphimorphia (46 spp.), Paucituberculata (2), Sirenia (1), Cingulata (5), Pilosa (8), Primates (42), Lagomorpha (2), Eulipotyphla (3), Carnivora (33), Perissodactyla (2), and Artiodactyla (47, including 32 cetaceans); 22 of these are endemic to Peru. Due to their high diversity and number of taxonomic changes, the Orders Chiroptera and Rodentia will be treated separately in future articles. The species records presented here, together with previous reports of bats (189 spp.) and rodents (189 spp.) yield a current total 569 species of mammals for Peru. Finally, we provide taxonomic notes for species that exhibit differences with respect to the previously published list of Peruvian mammals. We hope that this first list of mammals by department encourages further studies of Peruvian mammalian diversity at the regional level